The role of the family in personality formation - Pylkov E. A. (Humanitarian, 2018)
the article reveals such actual components of modern society as family, personality formation in the family, formation of the self-concept, life-purpose orientations of modern youth. One of the key moments in personality formation is movement, action. Formation involves personality development, both physically and spiritually from the very beginning of a person's life.
Keywords: самооценка; самоактуализация; самореализация; самоуважение; личностный рост; Я-концепция; self-esteem; self-actualization; self-concept; Self-realization; personal growth; самопостижение